2021
DOI: 10.1007/s00018-021-03795-w
|View full text |Cite
|
Sign up to set email alerts
|

RNA and DNA G-quadruplexes bind to human dicer and inhibit its activity

Abstract: Guanine (G)-rich single-stranded nucleic acids can adopt G-quadruplex structures. Accumulating evidence indicates that G-quadruplexes serve important regulatory roles in fundamental biological processes such as DNA replication, transcription, and translation, while aberrant G-quadruplex formation is linked to genome instability and cancer. Understanding the biological functions played by G-quadruplexes requires detailed knowledge of their protein interactome. Here, we report that both RNA and DNA G-quadruplexe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…), cations (i.e., K + ), and small molecule ligands [205], making RG4s highly dynamic. Very recent data underline a regulatory function played by RG4 in miRNA maturation through DROSHA-and Dicer-inhibition [206] and a potential role in physiological and pathological LLPS [207,208]. The presence of the RG4 structure in pre-miRNA exists in equilibrium with the canonical stem-loop structures, and this equilibrium regulates the maturation of some miRNAs, such as miR-92b [209].…”
Section: Conclusive Remarks and Future Perspectivesmentioning
confidence: 99%
“…), cations (i.e., K + ), and small molecule ligands [205], making RG4s highly dynamic. Very recent data underline a regulatory function played by RG4 in miRNA maturation through DROSHA-and Dicer-inhibition [206] and a potential role in physiological and pathological LLPS [207,208]. The presence of the RG4 structure in pre-miRNA exists in equilibrium with the canonical stem-loop structures, and this equilibrium regulates the maturation of some miRNAs, such as miR-92b [209].…”
Section: Conclusive Remarks and Future Perspectivesmentioning
confidence: 99%
“…All the studies indicate that rG4s in the pre-miRNAs compete with the stem-loop structures recognized by Dicer, thus inhibiting Dicer-mediated maturation and consequently reducing the mature miRNAs levels [26][27][28][29][30][31][32][33]. In addition, a recent report demonstrated that G4s bind to Dicer and inhibit its activity [34]. The formation and function of rG4s in mature miRNAs has been also reported in several works, suggesting a role in impairing miRNA binding to target mRNAs [35][36][37].…”
Section: Introductionmentioning
confidence: 74%
“…Importantly, in a cell, ASOs can interact not only with RNAs (hybridization-dependent interactions) but also with proteins (hybridization-independent interactions), which may lead to unintended side effects ( 66 ). Considering Dicer, the results of our previous studies indicated that human Dicer is able to bind 14 nt oligomers and longer species ( 67 , 68 ). Additionally, oligonucleotides binding to Dicer have the potential to influence its pre-miRNA cleavage activity, acting as competitive or allosteric inhibitors ( 59 ).…”
Section: Resultsmentioning
confidence: 99%